The Endocrine Disruptor Bisphenol A (BPA) Affects the Enteric Neurons Immunoreactive to Neuregulin 1 (NRG1) in the Enteric Nervous System of the Porcine Large Intestine - Szymańska, Kamila (Int J Mol Sci, 2020)
The enteric nervous system (ENS), located in the wall of the gastrointestinal (GI) tract, is characterized by complex organization and a high degree of neurochemical diversity of neurons. One of the less known active neuronal substances found in the enteric neurons is neuregulin 1 (NRG1), a factor known to be involved in the assurance of normal development of the nervous system. During the study, made up using the double immunofluorescence technique, the presence of NRG1 in the ENS of the selected segment of porcine large intestine (caecum, ascending and descending colon) was observed in physiological conditions, as well as under the impact of low and high doses of bisphenol A (BPA) which is commonly used in the production of plastics. In control animals in all types of the enteric plexuses, the percentage of NRG1-positive neurons oscillated around 20% of all neurons. The administration of BPA caused an increase in the number of NRG1-positive neurons in all types of the enteric plexuses and in all segments of the large intestine studied. The most visible changes were noted in the inner submucous plexus of the ascending colon, where in animals treated with high doses of BPA, the percentage of NRG1-positive neurons amounted to above 45% of all neuronal cells. The mechanisms of observed changes are not entirely clear, but probably result from neurotoxic, neurodegenerative and/or proinflammatory activity of BPA and are protective and adaptive in nature.